Arabidopsis mutants reveal that short- and long-term thermotolerance have different requirements for trienoic fatty acids - Routaboul, Jean-Marc (Journal of experimental botany, 2012)
The photosynthetic thylakoid has the highest level of lipid unsaturation of any membrane. In Arabidopsis thaliana plants grown at 22°C, approximately 70% of the thylakoid fatty acids are trienoic - they have three double bonds. In Arabidopsis, and other species, the levels of trienoic fatty acids decline substantially at higher temperatures. Several genetic studies indicate that reduced unsaturation improves photosynthetic function and plant survival at high temperatures. Here, these studies are extended using the Arabidopsis triple mutant, fad3-2 fad7-2 fad8 that contains no detectable trienoic fatty acids. In the short-term, fluorescence analyses and electron-transport assays indicated that photosynthetic functions in this mutant are more thermotolerant than the wild type. However, long-term photosynthesis, growth, and survival of plants were all compromised in the triple mutant at high temperature. The fad3-2 fad7-2 fad8 mutant is deficient in jasmonate synthesis and this hormone has been shown to mediate some aspects of thermotolerance; however, additional experiments demonstrated that a lack of jasmonate was not a major factor in the death of triple-mutant plants at high temperature. The results indicate that long-term thermotolerance requires a basal level of trienoic fatty acids. Thus, the success of genetic and molecular approaches to increase thermotolerance by reducing membrane unsaturation will be limited by countervailing effects that compromise essential plant functions at elevated temperatures